The Government Assurance and Annuity Acts, 16& 17 Vic. cap 45; 27 & 28 Vic. cap. 43 - O'Shaughnessy, Michael John (Statistical and Social Inquiry Society of Ireland, 1867)
The habit of Life Assurance is now almost universal among the wealthier classes, who every day appreciate its uses more and more; but unfortunately its benefits rarely reach the poor, who stand much more in need of them. The small premiums which they can pay; still more, the small sums in which those premiums must be collected, and the facilities for fraud and personation given by a number of small assurances, constitute difficulties impossible to overcome. A poor man has little or no property; his only capital is his labour, the profit of which diminishes as his need for it increases. The capitalist, as he grows old, enjoys the fruits of his accumulations; but the labourer finds that advancing years deprive him of the only capital he possessed. If he dies early, he leaves probably a widow and a helpless family without any means of support. If he lives long, he finds, as years roll on, that exhausted nature gives way under burthens which the vigour of youth hardly enabled it to support. Thus in many cases he is obliged to end his cheerless existence in the poor-house.
Read Tuesday, 20th February, 1866
Keywords: Life assurance; Government assurance and anniuty acts; 314.15